Acoustic barriers as an acoustic deterrent for native potamodromous migratory fish species. Issue 1 (10th December 2018) - Jesus, Joaquim; Amorim, Maria Clara P.; Fonseca, Paulo J.; Teixeira, Amílcar; Natário, Silvestre; Carrola, João; Varandas, Simone; Torres Pereira, Luís; Cortes, Rui M. V.
Abstract : This study focused on the use of sound playbacks as acoustic deterrents to direct native potamodromous migratory species away from all kind of traps. The effects of two acoustic treatments, a repeated sine sweep up to 2 kHz (sweep‐up stimulus) and an intermittent 140 Hz tone, were tested in three fish species native to Iberia: Salmo trutta, Pseudochondrostoma duriense and Luciobarbus bocagei . In contrast with S. trutta, the endemic cyprinids P. duriense and L. bocagei exhibited a strong repulse reaction to the frequency sweep‐up sound. The 140 Hz stimulus did not seem to alter significantly the behaviour of any of the studied species. These results highlight the potential of acoustic stimuli as fish behavioural barriers and their application to in situ conservation measures of native Iberian fish populations, to protect them from hydropower dams. In addition, this study shows that acoustic deterrents can be used selectively on target species.